Predicting The Number of Passengers on CV. MAKMUR Using The Backpropagation Method - Dewi Wahyuni (Cattleya Darmaya Fortuna, 2019)
Often, the number of passengers up and down at the CV company. Backpropagation is one solution to the problem. The number of passengers can be predicted so that the company CV. Prosperous have a large income. Based on the research, it was stated that MSE at the time of training predicted the number of passengers on CV. Makmur Medan was 0.000999. Based on the coefficient value in the training process, it can be concluded that ANN can predict the number of passengers well.